PUSAT VIDEO GAME DAN ANIMASI DI YOGYAKARTA DENGAN PENDEKATAN ARSITEKTUR METAFORA - Prima Setiawan Hartoyo; Widi Suroto; Fauzan Ali Ikhsan (Universitas Sebelas Maret Surakarta, 2014)
Abstract: The development of information and technology are rapidly giving a major influence on many areas of industry, one of the industry is video games and animation, therefore ther is a need for a place that can accommodate activities in the field of video games and animation. Video Games and Animation Center in Yogyakarta is a place that serves to accommodate all industrial activities in the field of video games and animation to enhance the potential of the industry in Yogyakarta. These activities include production activities , educational activities , promotional activities , and recreational activities for the general public. The goal of the Video Games and Animation Center that is intended for people who want to learn and create games and animations, games and animation studio production who want to promote their products, as well as a gathering place for the community of gamers and animation to socialize. The goal is to create a physical place as a place of production , education, promotion , and recreation in order to increase people's appreciation for video games and animation industry by providing infrastructure facilities required as well as providing a place for socialization for gamers and animation community using metaphor architecture approach to the realization of the building form. The approach chosen so that the characteristic and elements of metaphorical architecture of a video game and animation can appear in the form of a building with an analogy of form/ element on an object that is associated with video games and animation. Key words: Studio Production, Video Games, Animation, Metaphore Architectural Approach